The Funcitonalization of in Absentia Court as a Form of Corruption Crime’s Asset Recovery - Raffky Ariansyah; Sunarto Sunarto; Sanusi Husin; Dwi Nurahman (Corruptio, 2021)
Examination of corruption cases in the absence of the defendant at trial still has many obstacles. The elucidation of Law Number 31 of 1999 as amended in Law Number 20 of 2001 concerning eradicating criminal acts of corruption, especially in Article 38, provides an opening for the judiciary in absentia as an orientation to save state assets. What is the importance of the judiciary in absentia as an effort to recover assets, how is the implementation of justice in absentia to recover assets? What is the basis for the judges' legal considerations on the implementation of the trial? Then this study uses a normative research method with a normative juridical approach, while this type of research is descriptive. Based on the discussion in the study that the importance of the in absentia judiciary as an effort to recover assets carried out by the defendant legally and appropriately summoned to eradicate the crime of corruption and recover state losses can still be implemented, the assets and all assets of the defendant based on the verdict are proven to be related to corruption. A criminal act of corruption can then be executed. The implementation of the judiciary in absentia is an effort to recover assets through a legal process by taking into account the defendant's rights. The judiciary without the presence of the defendant is guided by Law Number 31 of 1999 as amended in Law Number 20 of 2001 concerning the eradication of criminal acts of corruption in Article 38 paragraph (1). The basis for the Judge's legal considerations regarding the trial examination in the defendant's absence is to ensure legal certainty so that the prosecutor as the executor can save the country's assets with considerations of exceptionality, return, and rescue of state assets.